Contagious capitalism : globalization and the politics of labor in China - Gallagher, Mary Elizabeth, 1969- (Princeton University Press, 2007)
One of the core assumptions of recent American foreign policy is that China's post-1978 policy of "reform and openness" will lead to political liberalization. This book challenges that assumption and the general relationship between economic liberalization and democratization. Moreover, it analyzes the effect of foreign direct investment (FDI) liberalization on Chinese labor politics. Market reforms and increased integration with the global economy have brought about unprecedented economic growth and social change in China during the last quarter of a century. Contagious Capitalism contends th